Current-Mode CCII+ Based Oscillator Circuits using a Conventional and a Modified Wien-Bridge with All Capacitors Grounded - J. Bajer; A. Lahiri; D. Biolek (Radioengineering, 2011)
The paper deals with a pair of current-mode sine-wave oscillator circuits. Both these circuits are implemented using positive second-generation current conveyors (CCII+). The principle of the first oscillator is based on a conventional Wien-bridge network. However, this implementation suffers from the use of a floating capacitor, which can be unacceptable in the case of on-chip integration. This drawback is solved in the second variant via a slight modification of the Wien-bridge network, which then allows the use of all capacitors grounded. The modified circuit version was manufactured by means of the socalled diamond transistors, which play the role of CCII+ active building blocks. The circuit behavior was analyzed theoretically, with particular emphasis on the identification of real effects and their elimination, and subsequently verified experimentally. The experimental results are included in the paper.